2013
DOI: 10.1177/096369351302200303
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of Curvature Effect on the Laminated Composites at Low Velocity Impact

Abstract: The aim of this study is to investigate experimentally effects of curvature, fibre orientation and ageing process on the low velocity impact behaviour of E-glass/epoxy composites. To investigate ageing effect, the half of the specimens have been left to dry at room condition and the other half was aged by the salt spray test. An apparatus was designed and produced to conduce impact tests of curved specimens. 20 J impact energy was used for experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…19,20 They include an analysis of the laminate defectiveness by way of a simultaneous measurement of the vibration and the acoustic pressure. 21,22 Very strong effect of curvature on low velocity impact of the laminate was found in study: 23 decrease in deflection and ability to absorb energy was found due to bending of fibres during fabrication. Thorough analysis results for the deformation and deformability of preforms as well as the properties of laminates produced on the basis of deformed preforms were presented by Lomov et al in a monumental publication series.…”
Section: Introductionmentioning
confidence: 91%
“…19,20 They include an analysis of the laminate defectiveness by way of a simultaneous measurement of the vibration and the acoustic pressure. 21,22 Very strong effect of curvature on low velocity impact of the laminate was found in study: 23 decrease in deflection and ability to absorb energy was found due to bending of fibres during fabrication. Thorough analysis results for the deformation and deformability of preforms as well as the properties of laminates produced on the basis of deformed preforms were presented by Lomov et al in a monumental publication series.…”
Section: Introductionmentioning
confidence: 91%